The Advantages and Disadvantages of E-Learning from the Viewpoints of Educational Faculty Students - الزعبي, ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aims to investigate the advantages and disadvantages of e-learning from the viewpoints of Jordanian students attending the Educational Sciences Faculty of Al al-Bayt University (AABU). The researcher used mixed approaches, therefore 11 participants were interviewed, and a questionnaire was designed consisting of (31) items distributed into two fields: the advantages (13 items) and disadvantages of e-learning (18 items), and then delivered to the study’s sample which was chosen randomly with a size of (300) students. The results showed that 55% of AABU students are not satisfied with electronic learning. The results additionally revealed that the students’ attitudes towards e-learning’s disadvantages were high, but were medium for e-learning’s advantages. There are statistically significant differences in the participants’ perceptions of e-learning disadvantages in favor of females. No statistically significant differences were detected in terms of the participants’ views towards the e-learning advantages according to the variables of gender and academic level